Distribution of genes encoding virulence factors and molecular analysis of Shigella spp. isolated from patients with diarrhea in Kerman, Iran. (March 2016) - Hosseini Nave, Hossein; Mansouri, Shahla; Emaneini, Mohammad; Moradi, Mohammad
Abstract: Shigella is one of the important causes of diarrhea worldwide. Shigella has several virulence factors contributing in colonization and invasion of epithelial cells and eventually death of host cells. The present study was performed in order to investigate the distribution of virulence factors genes in Shigella spp. isolated from patients with acute diarrhea in Kerman, Iran as well as the genetic relationship of these isolates. A total of 56 isolates including 31 S. flexneri, 18 S. sonnei and 7 S. boydii were evaluated by polymerase chain reaction (PCR) for the presence of 11 virulence genes ( ipaH, ial, set1A, set1B, sen, virF, invE, sat, sigA, pic and sepA ). Then, the clonal relationship of these strains was analyzed by multilocus variable-number tandem repeat analysis (MLVA) method. All isolates were positive for ipaH gene. The other genes include ial, invE and virF were found in 80.4%, 60.7% and 67.9% of the isolates, respectively. Both set1A and set1B were detected in 32.3% of S. flexneri isolates, whereas 66.1% of the isolates belonging to different serogroup carried sen gene. The sat gene was present in all S. flexneri isolates, but not in the S. sonnei and S. boydii isolates. The result showed, 30.4% of isolates were simultaneously positive and the rest of the isolates were negative for sepA and pic genes. The Shigella isolates were divided into 29 MLVA types. This study, for the first time, investigated distribution of 11 virulence genes in Shigella spp. Our results revealed heterogeneity of virulence genes in different Shigella serogroups. Furthermore, the strains belonging to the same species had little diversity. Highlights: 31 Shigella flexneri, 18 Shigella sonnei and 7 Shigella boydii were evaluated for the presence of 11 virulence gene. All isolates were positive for ipaH gene, but the sat gene was only present in S. flexneri isolates. The ial, invE and virF genes were found in 80.4%, 60.7% and 67.9% of the isolates, respectively. The Shigella isolates were divided into 29 MLVA types. Our results revealed heterogeneity of virulence genes in different Shigella serogroups.